Penerapan ROM (Range Of Motion) Aktif Kaki Untuk Meningkatkan Sensitivitas Kaki Pada Pasien DM - Riyan Al Rizki Firmansyah; Tri Siwi Kusumaningrum; Yeni Yarnita; Chairil; Wiwik Norlita (As-Shiha: Jurnal Kesehatan, 2025)
Background: Diabetes Mellitus (DM), which occurs due to uncontrolled blood glucose levels, can cause neuropathy, especially in the lower extremities, resulting in decreased or loss of foot sensitivity. Research Objective: This study aims to determine sensitivity after ROM. Research Method: This study used a direct assessment method with respondents and data collection. Research Results: The results of this study indicate that after performing Active Foot Range of Motion (ROM), foot sensitivity can be increased and numbness and tingling can be eliminated. Conclusion: Providing non-invasive therapy Pharmacological interventions in the form of Active Foot ROM (ROM) can be used as an alternative to increase foot sensitivity and can be applied independently by people with diabetes.